2020
DOI: 10.1093/ckj/sfaa109
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019: acute Fanconi syndrome precedes acute kidney injury

Abstract: Background Recent data have shown that severe acute respiratory syndrome coronavirus 2 can infect renal proximal tubular cells via Angiotensin Converting Enzyme 2 (ACE2) . Our objective was to determine whether Fanconi syndrome is a frequent clinical feature in coronavirus disease 2019 (COVID-19) patients. Methods A retrospective cohort of 42 laboratory-confirmed COVID-19 patients without history of kidney disease hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 27 publications
8
66
2
5
Order By: Relevance
“…One of the hypotheses for the occurrence of acute renal damage is the inadequacy of the inflammatory response linked to the cytokine storm observed in severe forms of COVID-19 and their effect on hypoperfusion of renal tubules [30] . A recent study reported that patients with severe COVID-19 have a high risk of developing Fanconi syndrome, leading to potentially life-threatening plasma disturbances [31] . SARS-CoV-2 infects the cells through its binding to the membrane-bound form of receptor-angiotensin converting enzyme II (ACE2) and subsequent internalization of the complex by the host cell [ 1 , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the hypotheses for the occurrence of acute renal damage is the inadequacy of the inflammatory response linked to the cytokine storm observed in severe forms of COVID-19 and their effect on hypoperfusion of renal tubules [30] . A recent study reported that patients with severe COVID-19 have a high risk of developing Fanconi syndrome, leading to potentially life-threatening plasma disturbances [31] . SARS-CoV-2 infects the cells through its binding to the membrane-bound form of receptor-angiotensin converting enzyme II (ACE2) and subsequent internalization of the complex by the host cell [ 1 , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlighted the possible association between ACE-I or ARB use and a significant increase in both ARDS and AKI. The induction of ACE2 expression by RAS blockade might affect the binding of SARS-CoV-2 to kidney tissues, deteriorating renal function, considering that ACE2 is abundantly expressed in the proximal tubules of the kidney and type II alveolar epithelium of lung 34,35 . Little is known about the dose effect of RAS blockade in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It can be shed into the blood and tubular urine by ADAMS17 (ADAM metallopeptidase domain 17)—a disintegrin and metalloproteinase. 78 80 The levels of circulating ACE2, however, can increase moderately in several pathologies, including diabetes mellitus and cardiovascular disease. 25 Full-length ACE2 is widely expressed in the cell membrane of several organs, including kidneys, testicles, and the gastrointestinal tract.…”
Section: Binding Of Sars-cov-2 To Ace2 Receptors and Internalizationmentioning
confidence: 99%